2001
DOI: 10.1136/jmg.38.1.26
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterisation of four cases of intrachromosomal triplication of chromosome 15q11-q14

Abstract: Context-Chromosomalabnormalities that involve the proximal region of chromosome 15q occur relatively frequently in the human population. However, interstitial triplications involving one 15 homologue are very rare with three cases reported to date. Objective-To provide a detailed molecular characterisation of four additional patients with interstitial triplications of chromosome 15q11-q14. Design-Molecular analyses were performed using DNA markers and probes specific for the 15q11-q14 region. Setting-Molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
101
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(109 citation statements)
references
References 41 publications
8
101
0
Order By: Relevance
“…BP4 has been mapped between markers D15S1019 and D15S165 and BP5 between markers D15S165 and D15S144. 10,12,18,34 Indeed, a BP located distal to the marker D15S144 had previously been hypothesized, 18,34 but neither characterized nor delineated. Our results demonstrated that such a BP distal to BP5 exists and may be specific to translocations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BP4 has been mapped between markers D15S1019 and D15S165 and BP5 between markers D15S165 and D15S144. 10,12,18,34 Indeed, a BP located distal to the marker D15S144 had previously been hypothesized, 18,34 but neither characterized nor delineated. Our results demonstrated that such a BP distal to BP5 exists and may be specific to translocations.…”
Section: Discussionmentioning
confidence: 99%
“…It was initially located between markers D15S12 and D15S24 ( 33 , for review) and has been subsequently more precisely located between markers D15S931 and D15S1019. 12,20,31 Two other distal BPs, BP4 and BP5, which have not been fully characterized, are involved in cases of large 15q11 -q14 interstitial triplications and inv dup (15) chromosomes. BP4 has been mapped between markers D15S1019 and D15S165 and BP5 between markers D15S165 and D15S144.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the triplications could form by U-type exchanges between three chromatids. [26][27][28][29] One exchange between homologous chromatids would take place at the distal breakpoint region, the other at the proximal breakpoint region, between either sister chromatids or homologous chromosomes. Brewer et al 23 proposed a replicationbased mechanism, supported by yeast observations, involving the generation of a dimeric inverted circular intermediate.…”
Section: Discussionmentioning
confidence: 99%
“…D15S144). 9,22 These observations would suggest the existence of different repeat sequences involved in rearrangements affecting these regions.…”
Section: Introductionmentioning
confidence: 98%
“…19 ± 21 Two other breakpoint regions named BP4 and BP5 have been mapped distally to BP3, between markers D15S24 and D15S144, and seem to be implicated in cases of large 15q11-q14 duplications or triplications. 4,5,9,18,20,21 These distal regions appear to be more complex since breakpoint variability has been described (BP located distal to Figure 1 15q11-q14 chromosome rearrangements, breakpoint regions, and LCR15s clusters and copies. BP1 to BP5 breakpoints and class I (BP1) and class II (BP2) PWS/AS deletion types are shown.…”
Section: Introductionmentioning
confidence: 99%